Prevalence and factors associated with temporomandibular disorder in physiotherapy students: cross-sectional study (Research, Society and Development, 2021)
The aim of this study is to evaluate the prevalence and factors associated with TMD in students who completed the Physiotherapy course. This is a cross-sectional study, carried out with students from the eighth to the tenth period, through the application of questionnaires, aiming to identify the sociodemographic and academic profile, parafunctional habits, severity of TMD and the level of anxiety. The data were analyzed using the Statistical Package for the Social Sciences program The Linear Trend Test was applied and a significant value of p